PENGARUH ADSORBEN SERBUK KULIT PISANG KEPOK ( Musa Paradisiaca L.) DAN ARANG AKTIG GRANUL TERHADAP KUALITAS MINYAK JELANTAH - Putri, Chantika; Choiron, Miftahul; Wiyono, Andi Eko; Rusdianto, Andrew Setiawan; Mahardika, Nidya Shara (Jurnal Penelitian Sains dan Teknologi Indonesia, 2024)
Used cooking oil is cooking oil that has been damaged. Purification of used cooking oil can utilize additional adsorbents as additional materials for the adsorption process. This research aims to determine the effect of adding granulated activated charcoal adsorbents and kepok banana peel powder on the quality of used cooking oil and determine the best treatment based on the specified test parameters. The used cooking oil purification method used is neutralization and bleaching. Each treatment will be repeated 3 times and the data will be processed using the SPSS application. The research results show that purified used cooking oil has a brightness value (L*) ranging from 64.30 – 62.67. The yield value for each treatment ranged from 73.137% - 62.093%. The water content value in each treatment has a value ranging from 0.013% - 0.046%. The free fatty acid value in each treatment ranged from 0.188% - 0.137%. The peroxide value in each treatment ranged from 6.00 – 2.33 mEk O2/kg. Meanwhile, the organoleptic parameter for aroma has a value between 4.0 – 4.9 and color has a value between 3.8 – 4.3. So the best treatment using MPE is the A2B3 treatment (15 gr : 10 gr).